A compacted triple band antenna design for GSM, Wi-Fi and WiMAX communication schemes for information computation system. (16th April 2020) - Saravanakumar, R.; Vijaykumar, V.R.
Recently, wireless communication devices like mobile phones are becoming increasingly popular. The aim of this paper is to design an antenna which can excite triple band operation with appreciable impedance bandwidth to combine WLAN/WiMAX communication specifications simultaneously in one device. A compacted triple band antenna is designed for global system for mobile (GSM) communications, Wi-Fi and WiMax-based applications. The proposed design comprehends a rectangular ring and S-shaped strip committed to the feed line. The dimension of the antenna is relatively small (16 × 20 mm 2 ) and it can be operated over the frequency ranges of 1.6-1.85 GHz, 3.4-3.65 GHz and 4.95-5.8 GHz with reflection coefficient less than −10 dB. The measured and simulated results expose that the proposed antenna design can well be operated in three desired bands.